Design and experiment of vertical pneumatic fertilization system with spiral Geneva mechanism - Chen, Haibo; Zheng, Jingfu; Lu, Shaojie; Zeng, Shan; Wei, Silong (International Journal of Agricultural and Biological Engineering, 2021)
In the traditional fertilization method, a large amount of fertilizer is applied, which causes congestion easily. It is not conducive to the sustainable development of agriculture. In this work, a vertical pneumatic fertilization system with a spiral Geneva mechanism was designed according to the operational requirements of variable-rate and smooth fertilization. The uniformity in discharging fertilizer with different spiral angles was simulated and analyzed by extended discrete element method (EDEM) based simulation software, from where the spiral angle of the fertilizer discharge wheel was determined to be 45°. The fertilization system includes a fertilizer apparatus with a spiral Geneva mechanism, whose optimal performance parameters were obtained from the bench experiment. The accuracy and uniformity of the fertilizer application system were taken as the evaluation indicators. The linear relationships of the discharged amount of fertilizer with the rotational speed and the opening of the fertilizer discharging wheel were verified by both static blowing fertilization and field experiments. The static blowing experimental results show that the discharged amount of fertilizer has a high linear correlation and accuracy with both the opening and rotational speed, and the highest correlation occurs with the rotational speed. The rotational speed and opening have significant effects on the discharged amount of fertilizer and the average coefficient of variation. The effect of the rotational speed was the most significant. According to the model obtained by multiple regression fittings, the optimal parameters were determined when the average coefficient of variation was small, the rotational speed was 15.9 r/min and the opening was 34.4 mm. Therefore, the purpose of precise fertilization can be achieved by adjusting the opening or rotational speed in a way to get the exact amount of fertilizer discharged as required by the corresponding crops. The field experiment showed that the variation coefficient of each fertilizer discharged decreases first and then increases with an increasing opening under different rotational speeds, which is consistent with the theoretical value. When the opening was 40 mm or 50 mm, the variation coefficient reached the minimum value, which is far less than the qualified index of 7.8%. In the static blowing experiment and the dynamic field experiment, the stability of the fertilizer discharging device can be significantly enhanced with the utilization of the pneumatic conveying fertilizer. This study can provide a theoretical reference for parameter selection and optimization of vertical spiral fertilization systems.Keywords: precision fertilization, fertilizer apparatus, variable rate technology, spiral Geneva mechanism, simulation analysis, performance experimentDOI: 10.25165/j.ijabe.20211404.6575Citation: Chen H B, Zheng J F, Lu S J, Zeng S, Wei S L. Design and experiment of vertical pneumatic fertilization system with spiral Geneva mechanism. Int J Agric & Biol Eng, 2021; 14(4): 135–144.